2010
DOI: 10.1002/iub.295
|View full text |Cite
|
Sign up to set email alerts
|

High expression stability of microtubule affinity regulating kinase 3 (MARK3) makes it a reliable reference gene

Abstract: SummaryDifference in gene expressions is characteristic of the function of different cell types and those genes with low expression variance can be used as standards for quantitative gene expression studies. Microarray technology is used to study global gene expression within a cell; hence, represents a suitable source of data to mine for genes with low expression variance. The coefficient of variation (COV) of each gene was determined and a threshold of less than 0.1 COV was used to select stably expressed ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…For example, several studies had analyzed published microarray datasets for reference genes [63,64] and other biologically significant features [65]. Moreover, most of the 30 microarrays originated from studies that were representative of the type of experimental studies which we expect our predictor to be useful in.…”
Section: Resultsmentioning
confidence: 99%
“…For example, several studies had analyzed published microarray datasets for reference genes [63,64] and other biologically significant features [65]. Moreover, most of the 30 microarrays originated from studies that were representative of the type of experimental studies which we expect our predictor to be useful in.…”
Section: Resultsmentioning
confidence: 99%
“…The advantage of COV is its capability to analyse as large number of samples as required [23] as the number of calculations increases proportionally to the sample size, resulting in linear complexity. NormFinder uses residual analysis between sample subgroup variation and the overall variation of the expression dataset to evaluate the variation contributed by each gene in the entire dataset [20].…”
Section: Resultsmentioning
confidence: 99%
“…However, microarrays, which usually contain thousands of probes, present a good source of data for identifying reference genes [22]. A recent study had successfully identified MARK3 as a suitable reference gene in mouse liver using microarray analysis [23]. …”
Section: Introductionmentioning
confidence: 99%
“…The expression stability was evaluated based on the assumption that a lower CV value means lower variations of POI expression levels within each group. CV values equal to or less than 10% were used for selecting stable genes in a previous study,6 the same criterion was adopted in this study.…”
Section: Methodsmentioning
confidence: 99%